Teacher Performance Is Influenced By Leadership Style, Compensation And Organisational Commitment: A Case Study At Sinar Timur Junior High School, Batam - Dabur, Feliks; Leto , Fransiska (Journal of Management, Economic, and Accounting, 2025)
This research aims to determine the impact of the Leadrship Style, Compensation and the Organisational Commitment on Teacher Performance in Sinar Timur's junior high school Batam. Data collection techniques in this study the form of library studies, interview and disseminating questionnaires. Research conducted using samples as much as 10 respondents. The results of the study with a significant level of 5% showed that: (1) The leadership style variable a have effect on teacher performance, this is seen from the significant value of 0.000 smaller than 0.05 and the value of Tcount 12,695 > Ttable 2,306. (2) The compensation have effect on teacher performance, this is seen from the significant value of 0.002 smaller than 0.05 and Tcount 5,157 > Ttable 2,306. (3) The organizational commitment have effect on teacher performance, this is seen from the significant value of 0.000 smaller than 0.05 and Tcount 2,496 > Ttable 2,306. (4) The leadership style variable, compensational and organizational commitment together affect the teacher performance by 89,1% and the remaining 10,9% in influenced by other factors beyond the research variable used, this is evident from the value of Fcount 100,668 > Fteble 3.862 with significant 0.000 < 0,05.